Optimal operation of microgrid in the park considering carbon trading and the proportion of green electricity - LI Zhenkun; LI Yimu; LUO Xiao; WANG Wei; WEI Yanjun (Diance yu yibiao)
In the context of double carbon goals, the problem of large amounts of carbon emissions generated by the micro grid in the park has become increasingly prominent. To this end, this paper firstly constructs the infrastructure of the micro-grid carbon trading market in the park, and designs the quota mechanism and price mechanism of carbon trading for the primary and secondary markets of the micro-grid carbon trading in the park. Secondly, in order to improve the consumption of new energy on the power grid side and guide the purchase and sale of electricity, the green electricity proportion of the superior power grid in different periods of time is introduced in this paper. An optimization model with the minimum actual operation cost as the objective and a multi-objective optimization model based on combined weighting of game theory are established to dispatch the flexible resources in the microgrid of the park. Based on the designed carbon trading mechanism and the green electricity proportion of the superior power grid, the operation results of the park micro-grid example under the two optimization models are calculated. According to the analysis of the simulation results, it can be seen that the multi-objective optimization model based on the combination of game theory is more reasonable and subjective initiative, which has strong reference significance in the implementation of the actual park micro-grid optimization operation.